System of generation, accumulation and distribution of heat by radiant floor to attenuate the effect of frost in the high Andean areas of the Tacna region - Heredia Alvarez, Gabriela Isabel (2015)
In 2012, the high Andean areas of the Tacna Region endured temperatures of up to 22 degrees below zero during the winter season according to the Report of the National Meteorology and Hydrology Service (SENAMHI), with this temperature the historical record of Tacna was once again reached. Andean rural housing is extremely precarious, it does not have adequate insulation, a fact that allows cold air currents to enter it, it does not have a system to use the energy generated by the combustion of firewood during food preparation ; It has a dirt floor, a corrugated metal roof, thermal bridges (slits) through which cold air enters, the doors do not close hermetically, poor quality of the adobe, lack of reinforcements and others that make it vulnerable to the onslaught of nature (frost , rains and earthquakes). The objective of the project is to design a system for accumulating and distributing heat by radiation, taking advantage of the heat generated by the kitchen when cooking food. The research proposal is related to the use of heat generated by the kitchen to be used through the HIPOCAUSTO ROMANO OR ONCIOL COREANO system (ancestral techniques) floor heating system. As a result of research, it was determined that, using heating from the improved kitchen (heating element) and the incorporation of the radiant floor (heat accumulator element), it is possible to raise the temperature of the house up to 102C with respect to the temperature of the outside environment . The technical evidence resulting from this study suggests that it is possible to technically take advantage of the resources and materials of the High Andean Zone of Tacna, in order to provide a home that offers moderate temperature conditions, with a positive impact on health, quality of life and economy of the high Andean population. According to the experimental tests carried out, it shows us that this system can increase the room temperature by 27.5cm2, remaining almost constant until 8am the next day, using a 6kg mass of firewood